Analysis of Factors That Influence People's Buying Interest in Online Stores in Terms of Islamic Economics - Herlina Oktaviani; Ade Albayan; Juhadi Juhadi (International Journal of Economics, Management and Accounting (IJEMA), 2023)
The background to this research is that technological developments have spurred changes in individual habits, including the habit of carrying out buying and selling transactions. Currently, we have moved to an era where transactions are no longer carried out face-to-face, but rather via online media. There is no longer a need for meetings between sellers and buyers in the market, but simply using internet technology and direct transactions between sellers and buyers. The aim of this research is to analyze the factors that influence people's buying interest in online stores in terms of Islamic economics. The method used in this research is qualitative. The results of this research show that the Islamic Economic view of doing business online is permissible as long as there is no injustice, elements of usury and fraud. Islam allows buying and selling online as long as it has fulfilled the pillars of the contract in sharia rules, the important thing is that there is a seller and a buyer and also that the shighah or ijab qabul has been fulfilled where the consumer must agree to the written terms and conditions if the transaction process is to continue. When shopping online, the object of the contract must be clear and not harm either party. The contract used in the online shop business is the greeting contract, where the greeting contract is an order contract by paying first and the goods are delivered later, but the characteristics of the goods must be clear.